Pseudo-dynamic tests and numerical analysis of free from damage Multistorey Steel Buildings with innovative connections - Cavallaro, Giovanni Ferrante (2019)
One of the most widespread structural systems is represented by Moment Resisting Frames (MRFs). This structural system is made up of frames capable of resisting seismic actions through predominantly flexural tension states. The stiffness and lateral resistance of the system depend on the flexural strength of the members and the type of connection, while the development of the plastic hinges guarantee the dissipation of the seismic input energy. The location of the dissipative zones varies according to the design approach adopted, typically they develop in beams, columns and connections. The most widespread design philosophy is to have strong columns, weak beams and full-strength rigid connections with complete resistance restoration, in this way all the seismic energy tends to be dissipated by the plastic hinges at the ends of the beams and at the base of the columns of the first level. In order to overcome the traditional design approach, the present research work introduces a new type of beam-column connection capable of exhibiting a remarkable rigidity in service conditions (SLE) and able to exhibit a remarkable dissipative capacity when a rare seismic event occurs. The codes currently in force provide that for seismic events characterized by a period of return comparable with the useful life of the construction (frequent or occasional events) the structures remain in the elastic field ensuring that the seismic energy is completely dissipated through viscous damping. Vice versa, the seismic energy must be dissipated through plastic engagement of parts of the Pseudo dynamic tests and numerical analysis of free from damage multistorey steel buildings with innovative connections structure, with wide and stable hysteresis cycles, for rare and very rare seismic events with a return period of about 500 years. The development of the hysteresis involves structural damage that have to be such as not to lead to the collapse of the structure in order to guarantee the protection of the life of those who occupy the building. The prediction of the behaviour of the structure in non-linear field for rare seismic events represents an aspect that only experimental research can describe in depth by developing new analytical models and innovative design philosophies. The execution of quasi-static tests can provide useful information in order to investigate the nonlinear behaviour of the members and the assemblages even if the forces or the displacement histories applied during the tests do not correspond exactly to the actions that occur during a real seismic event. The information obtained through these test procedures is however useful for calibrating analytical models and comparing the behaviour of structural components. The execution of tests on real scale structures is the best way to investigate the global behaviour of a structural system. For a more complete knowledge about the response in the dynamic field, the pseudo-dynamic tests represent a test protocol able to provide information of the structural response of a component or of a structure in a dynamic field through a static test. The main purpose of this work, developed within the FREEDAM research project financed by the European Community, is to develop an innovative beam-column connection. These innovative connections are equipped with an additional damper able to dissipate the energy deriving from destructive seismic events. The FREEDAM beam-column connection, through an appropriate design of the various components, is able to withstand frequent earthquakes and rare events without causing damage to the structural elements.